Identification of a region required for TSC1 stability by functional analysis of TSC1 missense mutations found in individuals with tuberous sclerosis complex - den Dunnen Johan T; Povey Sue; Ekong Rosemary; Sampson Julian; Kwiatkowski David; Hoogeveen-Westerveld Marianne; Mozaffari Melika; van den Ouweland Ans; Halley Dicky; Nellist Mark (BMC, 2009)
Abstract Background Tuberous sclerosis complex (TSC) is an autosomal dominant disorder characterised by the development of hamartomas in a variety of organs and tissues. The disease is caused by mutations in either the TSC1 gene on chromosome 9q34, or the TSC2 gene on chromosome 16p13.3. The TSC1 and TSC2 gene products, TSC1 and TSC2, form a protein complex that inhibits signal transduction to the downstream effectors of the mammalian target of rapamycin (mTOR). Recently it has been shown that missense mutations to the TSC1 gene can cause TSC. Methods We have used in vitro biochemical assays to investigate the effects on TSC1 function of TSC1 missense variants submitted to the Leiden Open Variation Database. Results We identified specific substitutions between amino acids 50 and 190 in the N-terminal region of TSC1 that result in reduced steady state levels of the protein and lead to increased mTOR signalling. Conclusion Our results suggest that amino acid residues within the N-terminal region of TSC1 are important for TSC1 function and for maintaining the activity of the TSC1-TSC2 complex.